Multisystem outcomes and predictors of mortality in critically ill patients with COVID-19: Demographics and disease acuity matter more than comorbidities or treatment modalities. Issue 5 (19th May 2021) - Alser, Osaid; Mokhtari, Ava; Naar, Leon; Langeveld, Kimberly; Breen, Kerry A.; El Moheb, Mohamad; Kapoen, Carolijn; Gaitanidis, Apostolos; Christensen, Mathias A.; Maurer, Lydia R.; Mashbari, Hassan; Bankhead-Kendall, Brittany; et al.
Abstract : Supplemental digital content is available in the text. Abstract : BACKGROUND: We sought to describe characteristics, multisystem outcomes, and predictors of mortality of the critically ill COVID-19 patients in the largest hospital in Massachusetts. METHODS: This is a prospective cohort study. All patients admitted to the intensive care unit (ICU) with reverse-transcriptase–polymerase chain reaction–confirmed severe acute respiratory syndrome coronavirus 2 infection between March 14, 2020, and April 28, 2020, were included; hospital and multisystem outcomes were evaluated. Data were collected from electronic records. Acute respiratory distress syndrome (ARDS) was defined as PaO2/FiO2 ratio of ≤300 during admission and bilateral radiographic pulmonary opacities. Multivariable logistic regression analyses adjusting for available confounders were performed to identify predictors of mortality. RESULTS: A total of 235 patients were included. The median (interquartile range [IQR]) Sequential Organ Failure Assessment score was 5 (3–8), and the median (IQR) PaO2/FiO2 was 208 (146–300) with 86.4% of patients meeting criteria for ARDS. The median (IQR) follow-up was 92 (86–99) days, and the median ICU length of stay was 16 (8–25) days; 62.1% of patients were proned, 49.8% required neuromuscular blockade, and 3.4% required extracorporeal membrane oxygenation. The most common complications were shock (88.9%), acute kidney injury (AKI) (69.8%), secondary bacterial pneumonia (70.6%), and pressure ulcers (51.1%). As of July 8, 2020, 175 patients (74.5%) were discharged alive (61.7% to skilled nursing or rehabilitation facility), 58 (24.7%) died in the hospital, and only 2 patients were still hospitalized, but out of the ICU. Age (odds ratio [OR], 1.08; 95% confidence interval [CI], 1.04–1.12), higher median Sequential Organ Failure Assessment score at ICU admission (OR, 1.24; 95% CI, 1.06–1.43), elevated creatine kinase of ≥1, 000 U/L at hospital admission (OR, 6.64; 95% CI, 1.51–29.17), and severe ARDS (OR, 5.24; 95% CI, 1.18–23.29) independently predicted hospital mortality. Comorbidities, steroids, and hydroxychloroquine treatment did not predict mortality. CONCLUSION: We present here the outcomes of critically ill patients with COVID-19. Age, acuity of disease, and severe ARDS predicted mortality rather than comorbidities. LEVEL OF EVIDENCE: Prognostic, level III.